2008
DOI: 10.1007/s00467-007-0726-5
|View full text |Cite
|
Sign up to set email alerts
|

Improved renal survival in Japanese children with IgA nephropathy

Abstract: Since the beginning of the 1990s, Japanese medical practitioners have extensively prescribed angiotensin-converting enzyme (ACE) inhibitors for children with mild IgA nephropathy (IgA-N) and steriods for those with severe IgA-N. We have performed a retrospective cohort study to clarify whether the long-term outcome has improved in Japanese children with IgA-N. Renal survival was defined as the time from onset to end-stage renal disease (ESRD). We divided the study period into two time periods based on the occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 17 publications
3
49
0
Order By: Relevance
“…Coppo et al (17) found that presenting proteinuria was NS as an independent prognostic value in their trial when examined by a multivariate Cox model. Our recent analysis in 500 children with IgA nephropathy supported this result (14). There is a possibility that the proteinuria level at (20 -28).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Coppo et al (17) found that presenting proteinuria was NS as an independent prognostic value in their trial when examined by a multivariate Cox model. Our recent analysis in 500 children with IgA nephropathy supported this result (14). There is a possibility that the proteinuria level at (20 -28).…”
Section: Discussionmentioning
confidence: 62%
“…Even though this was a prospective observational study, factors after the initial RCT period were difficult to control between the two groups. Therefore, proper analyses of long-term follow-up data are important to evaluate disease outcome and treatment effectiveness (13,14). Valid statistical evaluation using a multivariate Cox model was thought to work effectively in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore focused on the relationship between the period of initial treatment and renal outcome since the density of treatment apparently differed between the 2 periods. Yata et al [25] have already applied this approach to pediatric patients with IgAN. They showed that the renal survival rates of patients diagnosed during the late (1990–2004) period were significantly better than those diagnosed during the early (1976–1989) period (15-year renal survival rates 98.8 vs. 80.1%, p = 0.008 by log-rank test), and that the year of diagnosis was a significantly independent factor for ESRD-free survival in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, fewer infants younger than 3 years of age have been diagnosed with IgA nephropathy. Yata et al (2008) identified the disease in a 2.5-year-old infant, suggesting that the development of this disease can be found at around 2 years of age. As for the 2311 cases in the Japan Renal Biopsy Registry from 24 institutions between July 2007 and December 2008, the number of IgA nephropathy patients under 6 years old was 5, and the youngest patient of IgA nephropathy was 4 years old (Sugiyama et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, mesangial interposition will be less prominent after steroid therapy in children. In the case of children's IgA nephropathy too, inflammatory cells mostly remit, and the condition transits from mesangiocapillary glomerulonephritis to mesangial proliferative glomerulonephritis after steroid therapy (Yata et al 2008). The present patient showed similar findings and may possibly progress to typical mesangial proliferative IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%